THE STUDY OF BENDING BEAMS MECHANICALS PROPERTIES WITH MICRO REINFORCEMENT - Yusra, Andi; Opirina, Lissa; Farizal, Teuku (JURNAL TEKNIK SIPIL, 2021)
research on fiber concrete is currently growing very rapidly. The alternative fibers used in the concrete mix-ture is to use natural fibers. In this study, researchers used bamboo fiber as a substitute for artificial fiber, where Bamboo has a good tensile strength. The aim of this study to increase beam strength in sustaining ex-ternal loads by added bamboo fibers. The content of fiber additional to the concrete mixture was 1.5% of the cement weight. The mix design of concrete using ratio of cement water 0.25. The plasticizer and filler added in the mixture with the content of 2% and 15% cement weight, respectively. Two reinforced concrete beam specimens and 24 concrete cylinder specimens used in the study. Tests carried out of 28 days, and 56 days for cylindrical concrete, while bending test conducted of CBR1 and CBR2 at 28 test life only. In study show that addition 1.5% bamboo fiber to reinforced concrete beams increased the flexural capacity and ductility of the beams